STRATEGI KONSELING LINTAS AGAMA DAN BUDAYA DI SEKOLAH - Sri Dwi Lestari; Zulkipli Lessy (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Even though there are counseling and guidance teachers in schools, problems still exist related to intolerance, so it is necessary to study and understand more about the strategies of cross-religious and cultural counseling in schools. This study aims to explore cross-religious and cultural counseling strategies in schools, to examine whether a multicultural school environment can tolerate diversities. The collection of data in this study is in the form of examination of books, journal articles, as well as internet sites that are related to the topic of discussion. After collected, data is analyzed to get conclusions. The results of this study are that the strategy of cross-religious and cultural counseling in schools show that counselors who are also educators must have a multicultural understanding, broad knowledge of multi-cultures and religions as well as have skills and effectiveness in counseling. This means that the counselors, apart from being professional in terms of knowledge, also have the right instinct regarding the approach to be used to assist cross-religious and cultural counseling in schools.